Cloud auditing best practices : perform security and IT audits across AWS, Azure, and GCP by building effective cloud auditing plans /: perform security and IT audits across AWS, Azure, and GCP by building effective cloud auditing plans. (2023) - Cambric, Shinesa; Ratemo, Michael
No abstract available